Are all antibiotic persisters created equal? - Shultis, Michael W.; Mulholland, Claire V.; Berney, Michael (Frontiers in Cellular and Infection Microbiology, 2022)
Antibiotic persisters are a sub-population of bacteria able to survive in the presence of bactericidal antibiotic despite the lack of heritable drug resistance mechanisms. This phenomenon exists across many bacterial species and is observed for many different antibiotics. Though these bacteria are often described as “multidrug persisters” very few experiments have been carried out to determine the homogeneity of a persister population to different drugs. Further, there is much debate in the field as to the origins of a persister cell. Is it formed spontaneously? Does it form in response to stress? These questions are particularly pressing in the field of Mycobacterium tuberculosis, where persisters may play a crucial role in the required length of treatment and the development of multidrug resistant organisms. Here we aim to interpret the known mechanisms of antibiotic persistence and how they may relate to improving treatments for M. tuberculosis, exposing the gaps in knowledge that prevent us from answering the question: Are all antibiotic persisters created equal?